2008
DOI: 10.1111/j.1467-8683.2008.00680.x
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Firm Value: The Case of Venezuela

Abstract: Manuscript Type: EmpiricalResearch Question/Issue: We examine the relationship between corporate governance and firm value, and evaluate the relatively understudied governance practices in Venezuela. Research Findings/Results: We construct a corporate governance index (CGI) for publicly-listed firms that is free of self-selection and self-reported bias and find that its mean value is below the emerging market average in general, and below the Latin American average in particular. This weak investor protection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
108
1
12

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 151 publications
(141 citation statements)
references
References 45 publications
10
108
1
12
Order By: Relevance
“…This is contrary to other studies (e.g. Klapper and Love, 2004, Garay and González, 2008, Balasubramanian et al, 2010) that found better corporate governance to be associated with higher company valuation. These contrasting results imply that, in our sample, the association between the governance index and company performance is contingent on how company performance is measured.…”
Section: Association Between Corporate Governance and Company Performcontrasting
confidence: 56%
See 4 more Smart Citations
“…This is contrary to other studies (e.g. Klapper and Love, 2004, Garay and González, 2008, Balasubramanian et al, 2010) that found better corporate governance to be associated with higher company valuation. These contrasting results imply that, in our sample, the association between the governance index and company performance is contingent on how company performance is measured.…”
Section: Association Between Corporate Governance and Company Performcontrasting
confidence: 56%
“…Based on the status of the legal systems and the enforcement of laws in these countries, it can be reasoned that corporate governance practices may not be as effective as they are in developed countries. However, a weak legal environment offers an opportunity for companies to differentiate themselves from the rest and send signals to attract investors by choosing, independently, to adopt good corporate governance practices (Garay andGonzález, 2008, Klapper andLove, 2004). There is empirical evidence suggesting that private enforcement mechanisms are often more effective than public ones (Berglöf and Claessens, 2006).…”
Section: Relevance Of Corporate Governance In Sub-saharan African Coumentioning
confidence: 99%
See 3 more Smart Citations